2006
DOI: 10.1073/pnas.0508582103
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of the base excision and nucleotide incision repair pathways reveals their respective biological roles

Abstract: The multifunctional DNA repair enzymes apurinic͞apyrimidinic (AP) endonucleases cleave DNA at AP sites and 3 -blocking moieties generated by DNA glycosylases in the base excision repair pathway. Alternatively, in the nucleotide incision repair (NIR) pathway, the same AP endonucleases incise DNA 5 of a number of oxidatively damaged bases. At present, the physiological relevance of latter function remains unclear. Here, we report genetic dissection of AP endonuclease functions in base excision repair and NIR pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 33 publications
4
61
0
Order By: Relevance
“…Several questions were addressed as to the new functions of APendonuclease: whether endonuclease activity for base damage is different from AP endonuclease activity, how active NIR is within human cells as compared with BER, and how AP endonucleases are able to recognize various types of base damage. For the first question, mutagenesis of the E. coli nfo gene showed that three mutants-H69A, H109A, and G149D-were proficient in the AP endonuclease and 3 0 phosphodiesterase activities but deficient in NIR activity, indicating that AP endonuclease and base damage nicking activities are separate mechanisms (Ishchenko et al 2006). These nfo mutants complemented the hypersensitivity of an E. coli nfo-deletion mutant to alkylation but not to oxidative DNA damage, suggesting that NIR is responsible for repair of oxidative base damage in E. coli cells.…”
Section: Nir Aer and Ssb Repairmentioning
confidence: 99%
“…Several questions were addressed as to the new functions of APendonuclease: whether endonuclease activity for base damage is different from AP endonuclease activity, how active NIR is within human cells as compared with BER, and how AP endonucleases are able to recognize various types of base damage. For the first question, mutagenesis of the E. coli nfo gene showed that three mutants-H69A, H109A, and G149D-were proficient in the AP endonuclease and 3 0 phosphodiesterase activities but deficient in NIR activity, indicating that AP endonuclease and base damage nicking activities are separate mechanisms (Ishchenko et al 2006). These nfo mutants complemented the hypersensitivity of an E. coli nfo-deletion mutant to alkylation but not to oxidative DNA damage, suggesting that NIR is responsible for repair of oxidative base damage in E. coli cells.…”
Section: Nir Aer and Ssb Repairmentioning
confidence: 99%
“…For example, APE1 has been found to initiate DNA glycosylase-independent repair of oxidized cytosines [20][21][22]. This alternate repair pathway has been defined as Nucleotide Incision Repair (NIR), yet can also be considered a minor sub-pathway of BER with a unique APE1-mediated repair initiation event.…”
Section: Introduction Of a Unifying Ber Modelmentioning
confidence: 99%
“…This mutant, which represents the counterpart of Nfo Mpn mutant H72N from this study, was found to lack one of the three active-site Zn 2+ ions (Zn 1 , as predicted) and also showed other rearrangements within the active site, such as an increased conformational flexibility of residue H109, which is, like H69, involved in the interaction with Zn 1 in the wild-type protein (Golan et al, 2010). Like Nfo Eco mutant H69A, Nfo Mpn mutant H72N showed a significantly reduced AP cleavage activity in comparison with the wild-type protein; however, both proteins showed considerably higher activities in the presence of divalent cations in the reaction (this study; Ishchenko et al, 2006 This notion is based on the finding that mutation of the aforementioned active site residues not only affects the AP endonucleolytic activity (in particular in the presence of EDTA), but also affects the exonucleolytic activity of Nfo Mpn . Nevertheless, it is clear that the latter activity has more stringent amino acid sequence and/or structural requirements than the AP cleavage activity.…”
Section: Discussionmentioning
confidence: 58%